Biology and Breeding of Food Legumes 2011
DOI: 10.1079/9781845937669.0220
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for biotic stresses.

Abstract: This chapter discusse the progress of and prospects through genetic enhancement in combating biotic stresses (pathogens, insect pests and nematodes) in important food legumes (including chickpea, lentil, mung bean, pigeon pea, cowpea and pea).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The utility of Bt ICPs in conferring resistance to varied pests has been demonstrated in a wide range of crops . In pigeonpea, major crop losses resulting in stagnated productivity are mainly due to various biotic and abiotic factors, including herbivory by H. armigera . A major impetus for the mitigation of this pest in pigeonpea has been transgenesis due to the lack of availability of resistance sources in the cultivated germplasm .…”
Section: Resultsmentioning
confidence: 99%
“…The utility of Bt ICPs in conferring resistance to varied pests has been demonstrated in a wide range of crops . In pigeonpea, major crop losses resulting in stagnated productivity are mainly due to various biotic and abiotic factors, including herbivory by H. armigera . A major impetus for the mitigation of this pest in pigeonpea has been transgenesis due to the lack of availability of resistance sources in the cultivated germplasm .…”
Section: Resultsmentioning
confidence: 99%
“…The abiotic stresses like heat, salinity, drought and cold are the major adverse environmental factors that limit plant productivity (Ahmad et al, 2014). While as, biotic stresses include diseases, insects, pests and plant-parasitic nematodes that drastically affect chickpea yield (Basandrai et al, 2011). The major diseases are Fusarium wilt (Fusarium oxysporumf.…”
Section: Issn: 2319-7706 Volume 10 Number 02 (2021)mentioning
confidence: 99%
“…Valdez (1989) observed only a slight effect of the host on larval survival, and Okech and Saxena (1990) indicated that stem and pods act as antibiosis component of resistance in TVNu 946 and VITA 5. In general, antibiosis consequences are expressed in terms of weight and size of insects, sex ratio, and proportion of insects entering diapause (Basandrai et al 2011). Four green gram accessions LM 131, V 1123, LM 371, and STY 2633 and three black gram accessions UH 82-5, IC 8219, and SPS 143 were found to be moderately resistant to bruchid C. chinensis having less percentage survival and prolonged developmental period as compared to susceptible check (Ponnusamy et al 2014).…”
Section: Antibiosismentioning
confidence: 99%